Teaching English Phonetics and Pronunciation to ESL Students and Non-English Speaking Residents - Swapna, M. (Recent Research Reviews Journal, 2023)
Pronunciation teaching is evolving as a result of an emerging trend in foreign language teaching to promote communicative and holistic approaches. Specifically, for the students coming from different cultural and linguistic backgrounds with a different life experience, pronunciation methodology and phonology have been recently adopted to improve the English pronunciation. This research study highlights the significance of English Pronunciation for English as a Second Language (ESL) students in India. This study also highlights the potential of teaching native English pronunciation and importance of English phonetics and phonology by finding out the factors that generally affects the pronunciation of ESL students with different mother tongues. In this research, a sample experiment has been conducted on school students. The student sample information is obtained via Selective Sampling Technique. From the resultant observations, this study suggests different communicative approaches, which are suitable for the ESL learners to enhance their English language pronunciation